N-terminal pro-brain natriuretic peptide in acute Kawasaki disease correlates with coronary artery involvement. - ADJAGBA, MAHOUNA PHILIPPE DOTOU; Desjardins, Laurent; Fournier, Anne; Spigelblatt, Linda; Montigny, Martine; Dahdah, Nagib (My University, 2015)
Background: We have lately documented the importance of N-terminal pro-brain natriuretic peptide in aiding the diagnosis of Kawasaki disease. Objectives: We sought to investigate the potential value of N-terminal pro-brain natriuretic peptide pertaining to the prediction of coronary artery dilatation (Z-score >2.5) and/or of resistance to intravenous immunoglobulin therapy. We hypothesised that increased serum N-terminal pro-brain natriuretic peptide level correlates with increased coronary artery dilatation and/or resistance to intravenous immunoglobulin. Methods: We carried out a prospective study involving newly diagnosed patients treated with 2 g/kg intravenous immunoglobulin within 5–10 days of onset of fever. Echocardiography was performed in all patients at onset, then weekly for 3 weeks, then at month 2, and month 3. Coronary arteries were measured at each visit, and coronary artery Z-score was calculated. All the patients had N-terminal pro-brain natriuretic peptide serum level measured at onset, and the Z-score calculated. Results: There were 109 patients enrolled at 6.58 ± 2.82 days of fever, age 3.79 ± 2.92 years. High N-terminal pro-brain natriuretic peptide level was associated with coronary artery dilatation at onset in 22.2 versus 5.6% for normal N-terminal pro-brain natriuretic peptide levels (odds ratio 4.8 [95% confidence interval 1.05–22.4]; p=0.031). This was predictive of cumulative coronary artery dilatation for the first 3 months (p =0.04–0.02), but not during convalescence at 2–3 months (odds ratio 1.28 [95% confidence interval 0.23–7.3]; p=non-significant). Elevated N-terminal pro-brain natriuretic peptide levels did not predict intravenous immunoglobulin resistance, 15.3 versus 13.5% (p =1). Conclusion: Elevated N-terminal pro-brain natriuretic peptide level correlates with acute coronary artery dilatation in treated Kawasaki disease, but not with intravenous immunoglobulin resistance.
Keywords: Kawasaki disease; prediction; coronary artery involvement; N-terminal pro-brain natriuretic peptide; predictive value